2011 International Conference on Computer Distributed Control and Intelligent Environmental Monitoring 2011
DOI: 10.1109/cdciem.2011.165
|View full text |Cite
|
Sign up to set email alerts
|

Study on Polypropylene Matrix Composites Filled with Glass Fiber Recycled from Waste Printed Circuit Board

Abstract: SDUWLFOH SDUWLFOH SDUWLFOH SDUWLFOH VL]H VL]H VL]H VL]H PDVV PDVV PDVV PDVV IUDFWLRQ IUDFWLRQ IUDFWLRQ IUDFWLRQ DQG DQG DQG DQG VXUIDFH VXUIDFH VXUIDFH VXUIDFH SUH SUH SUH SUHWUHDWPHQW WUHDWPHQW WUHDWPHQW WUHDWPHQW RQ RQ RQ RQ WKH WKH WKH WKH SURSHUW SURSHUW SURSHUW SURSHUWLHV LHV LHV LHV RI RI RI RI FRPSRVLWHV FRPSRVLWHV FRPSRVLWHV FRPSRVLWHV ZDV ZDV ZDV ZDV UHVHDUFKHGUHVHDUFKHG UHVHDUFKHG UHVHDUFKHG UHVSHFWLYHO\ UHVSHFWLYHO\ UHVSHFWLYHO\ UHVSHFWLYHO\ 7KH 7KH 7KH 7KH UHVXOW UHVXOW UHVXOW UHVXOWV V V V KDYH KD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Another recent study done by Liang and his co-workers found that the molecular chain of polyolefin (PP,PE etc.) is lack of active groups, so it is hardly to form effective interface adhesion because of its poor affinity composite with glass fibers, as a result, stress cannot be transferred to glass fibers well by matrix resin [ 9 ]. The enhancement of glass fiber weakens greatly, and this will also influence the performances of the composites.…”
Section: Resultsmentioning
confidence: 99%
“…Another recent study done by Liang and his co-workers found that the molecular chain of polyolefin (PP,PE etc.) is lack of active groups, so it is hardly to form effective interface adhesion because of its poor affinity composite with glass fibers, as a result, stress cannot be transferred to glass fibers well by matrix resin [ 9 ]. The enhancement of glass fiber weakens greatly, and this will also influence the performances of the composites.…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly WPCBs material is FR-4 which using glass fibers as the reinforcing materials and brominated epoxy resins (BERs) as a binder [1,2]. BERs containing a large number of brominated flame retardants (5%-15%, BFRs) which are widely used in the PCBs to reduce the possibility of fire under the thermal stress [3].…”
Section: Introductionmentioning
confidence: 99%